Possible Worlds in Ken Kesey’s One Flew over the Cuckoo’s Nest - Amani, Omid; Pirnajmuddin, Hossein; Hanif, Mohsen (Humanities Diliman: A Philippine Journal of Humanities, 2020)
In this paper the authors apply Marie-Laure Ryan’s Possible-Worlds theory to Ken Kesey’s One Flew over the Cuckoo’s Nest to show how the characters’ different conceptions of the world define and build up the narrative structure of the novel. The objective is to look into how the characters in Kesey’s novel fall into different types of alternative possible worlds, namely Knowledge worlds, Prospective Extensions of Knowledge worlds, Intention worlds, Obligation worlds, Wish worlds, and Fantasy Universes. Also examined is the internal structure of the fictional worlds or, in Ryan’s terminology, “the textual actual world,” to explicate the internal conflicts between the actual domain and the private worlds of the different characters. The paper finally concludes with some reflections on these worlds’ interactions and their conflicts, and on the way they contribute to plot development and consolidate, in Ryan’s terms, its “tellability.”
Keywords: Ken Kesey, One Flew over the Cuckoo’s Nest, Marie-Laure Ryan, Possible Worlds Theory, Internal Structure of Fictional Worlds, tellability